A variation on strongly lacunary ward continuity - Sönmez, Ayşe; Çakallı, Hüseyin (Universitatii Al.I.Cuza din Iasi Carol I, no. 11 Iasi 700506, 2016)
A function f defined on a subset A of a cone normed space X is strongly lacunary ward continuous if it preserves strongly lacunary quasi-Cauchy sequences of points in A; that is, (f (xk)) is a strongly lacunary quasi-Cauchy sequence whenever (xk) is strongly lacunary quasi-Cauchy. In this paper, not only strongly lacunary ward continuity, but also some other kinds of continuities are investigated in cone normed spaces. © 2018 Elsevier B.V., All rights reserved.
Keywords: Cone normed spaces; Continuity; Quasi-cauchy sequences; Strongly lacunary convergence